2018
DOI: 10.1111/petr.13341
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of kidney transplants in pediatric patients with the vertebral defects, anal atresia, cardiac defects, tracheoesophageal fistula, renal anomalies, limb abnormalities association

Abstract: In this single‐center retrospective study, we analyzed kidney transplant outcomes in nine pediatric patients with VACTERL [vertebral defects, anal atresia, cardiac defects, tracheoesophageal fistula, renal anomalies, limb abnormalities] association—making this the largest study of its kind. Of 743 pediatric kidney transplant recipients at our center (1980‐2017), nine had documented diagnoses of VACTERL association. All nine had congenital anorectal malformations and renal anomalies, five had vertebral defects,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Diagnosing occult renal anomalies is equally important, as these malformations may increase the risk of future morbidity such as chronic renal insufficiency, even in the absence of NB. Moreover, some studies have raised the hypothesis that patients with the VACTERL association progress to endstage renal failure at an increased rate and present a higher incidence of complications compared with non-VACTERL patients with kidney disease and have an increased incidence of post-transplant urologic complications (Ahn et al, 2009;Diaz et al, 2019). Akl et al (2015) showed that NB was the cause of 25% of children with end-stage renal failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosing occult renal anomalies is equally important, as these malformations may increase the risk of future morbidity such as chronic renal insufficiency, even in the absence of NB. Moreover, some studies have raised the hypothesis that patients with the VACTERL association progress to endstage renal failure at an increased rate and present a higher incidence of complications compared with non-VACTERL patients with kidney disease and have an increased incidence of post-transplant urologic complications (Ahn et al, 2009;Diaz et al, 2019). Akl et al (2015) showed that NB was the cause of 25% of children with end-stage renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…Akl et al (2015) showed that NB was the cause of 25% of children with end-stage renal failure. In the study conducted by Diaz et al (2019), 67% of a cohort of VACTERL patients that underwent renal transplants had NB. Ahn et al (2009), in a study of children with VACTERL association and chronic kidney disease, 5 of 12 (41.6%)…”
Section: Discussionmentioning
confidence: 99%